Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pengunjung Rahmat International Wildlife Museum and Gallery - Alya Rahmita; Vivianti Novita; Harris Pinagaran Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Rahmat International Wildlife Museum and Gallery which is the first wildlife museum in Southeast Asia and even in the world, precisely on Jalan S.Parman. Service quality is an effort to fulfill the needs and desires of consumers and the accuracy of their delivery in balancing consumer desires. Price is the amount of money charged for a product, or the amount of value that customers exchange for the benefits of owning or using it. This study analyzes the effect of service quality and price on visitor satisfaction at Rahmat International Wildlife Museum and Gallery. Data from 100 respondents were analyzed using multiple linear regression methods. The results showed that service quality has a positive and significant effect on visitor satisfaction (tcount = 4.366, p < 0.05). Price also has a positive and significant effect on visitor satisfaction (tcount = 4.188, p < 0.05). Together, service quality and price have a positive and significant effect on visitor satisfaction (Fcount = 49.967, p < 0.05). The results of this study provide important insights for museum managers to increase visitor satisfaction with good service quality and competitive prices, attract more visitors, and ensure repeat visits in the future. Service quality and price have an important role in determining visitor satisfaction in this museum.